2015
DOI: 10.4081/gh.2015.349
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of fasciolosis in dairy cow herds in Munster province of Ireland and detection of major climatic and environmental predictors of the exposure risk

Abstract: Abstract. Fasciolosis caused by Fasciola hepatica is a widespread parasitic disease in cattle farms. The aim of this study was to detect clusters of fasciolosis in dairy cow herds in Munster Province, Ireland and to identify significant climatic and environmental predictors of the exposure risk. In total, 1,292 dairy herds across Munster was sampled in September 2012 providing a single bulk tank milk (BTM) sample. The analysis of samples by an in-house antibody-detection enzyme-linked immunosorbent assay (ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
(32 reference statements)
3
8
0
1
Order By: Relevance
“…These results are in accordance with findings indicating that major predictors of liver exposure included (i) the total number of wetdays (Selemetas et al, 2015a,b), (ii) the rainfall in August (McCann et al, 2010a;Selemetas et al, 2015b) which is vital for the development of the intermediate snail-host and parasite (Torgerson and Claxton, 1999), and (iii) the rainfall in September (McCann et al, 2010a) highlighting the importance of wet pastures for the intermediate snail-host. Finally, it is important to stress the negative correlation of liver fluke exposure risk with rainfall levels in August.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in accordance with findings indicating that major predictors of liver exposure included (i) the total number of wetdays (Selemetas et al, 2015a,b), (ii) the rainfall in August (McCann et al, 2010a;Selemetas et al, 2015b) which is vital for the development of the intermediate snail-host and parasite (Torgerson and Claxton, 1999), and (iii) the rainfall in September (McCann et al, 2010a) highlighting the importance of wet pastures for the intermediate snail-host. Finally, it is important to stress the negative correlation of liver fluke exposure risk with rainfall levels in August.…”
Section: Discussionsupporting
confidence: 93%
“…Under the temperate Irish climate these findings may underline the need for a consistent set of optimal conditions of moisture and soil type for the survival and development of the free-living stages of F. hepatica and the intermediate snail host, including embryonation, hatching of miracidia, and the emergence of cercariae from snails (Torgerson and Claxton, 1999). These differences in climatic and environmental variables were consistent with the findings of studies, which suggested that rainfall Yilma and Malone, 1998;McCann et al, 2010a,b;Bennema et al, 2011;Martins et al, 2012), total wetdays (McCann et al, 2010a;Selemetas et al, 2015a) and raindays (Selemetas et al, 2015a), NDVI (Fuentes, 2004;Fuentes et al, 2005;Fuentes, 2006;Durr et al, 2005;Selemetas et al, 2015b), temperature Yilma and Malone, 1998;Bossaert et al, 1999;McCann et al, 2010a,b;Martins et al, 2012) and soil type (McCann et al, 2010a;Selemetas et al, 2015a) may play a role in the exposure to liver fluke. In addition, the association of poorly drained soils with high-risk clusters reflects the importance of impeded drainage to the transmission of fasciolosis, which is in accordance with the positive association between poor drainage and disease risk .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Vanaf het begin van de maand juli is er een piek in het aantal volwassen leverbotslakken die na de maand juli afloopt tot eind september. Begin oktober tot eind december kan er opnieuw een piek voorkomen indien de weersomstandigheden zich daarvoor lenen (Charlier et al, 2014;Hourdin et al, 2006 (Caron et al, 2007;Fairweather, 2011;Mas-Coma et al, 2009;Selemetas et al, 2015a). Onderzoek toont aan dat de meeste slakken worden gevonden in greppels en licht moerasachtige grond (Charlier et al, 2014).…”
Section: Figuur 2 Uitbreiding Van De Leverbotresistentie Voor Triclabunclassified